ON FORMATION OF THINKING IN THE AREA OF NATURAL SCIENCES IN TEACHER´S TRAINING PROCESS - HORVATHOVA, Daniela; ZELENICKY, Lubomir (Trends in education, 2010)
Our contribution presents the structure and demonstrations of laboratory practice in which we try to integrate chosen information from physics and biology into the secondary grammar school's teaching plans. When proposing laboratory practice we try to consider the subject field in which the integrated knowledge and measurement methods are used. We try to focus on the integration of knowledge in the area of sense organs of humans (eye, ear), bees (eye) and their modelling. Laboratory practice is designed in the way to motivate the future teachers of natural sciences to work with specialized literature from particular subjects and to use Internet.
Keywords: natural science; laboratory practice; teacher.